Pengembangan Aplikasi Augmented Reality Untuk Memadukan Baju Kampanye (Studi Kasus: Calon Anggota DPRD Kabupaten Nganjuk) - Ananda Widya Pratama; Herman Tolle; Wibisono Sukmo Wardhono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Party dress is one of the identities of the party in every election, there is a group of people who wear uniform party dresses. Party clothes are used during campaigns to convey party messages and information to the public. The 2019 general election is a general election whose polling is the most complex and stunning of the world. It is this election system that raises challenges for the community because of simultaneous elections. The simultaneous election to elect the president and legislature is evident from the survey results of the Indonesian Survey Circle (2019) showing that